The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acsnano.5b04872
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic Switching of a Carbon Nanotube Chiral Junction Imaged with Nanometer Spatial Resolution

Abstract: Chiral junctions of carbon nanotubes have the potential of serving as optically or electrically controllable switches. To investigate optoelectronic tuning of a chiral junction, we stamp carbon nanotubes onto a transparent gold surface and locate a tube with a semiconducting-metallic junction. We image topography, laser absorption at 532 nm, and measure I-V curves of the junction with nanometer spatial resolution. The bandgaps on both sides of the junction depend on the applied tip field (Stark effect), so the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…These are the result of the short tip-sample distance on the order of nanometers required for quantum tunneling. 35 It has previously been shown that activation energies below 1 eV are sufficient to displace ions in the perovskite material and distort the perovskite lattice where the migration activation energies are the lowest for the halides followed by the A-site cations. [55][56][57][58] This results in various, and most of the time unpredictable and unforeseen, surface and bulk structures depending on the strength and polarity of the electric field.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are the result of the short tip-sample distance on the order of nanometers required for quantum tunneling. 35 It has previously been shown that activation energies below 1 eV are sufficient to displace ions in the perovskite material and distort the perovskite lattice where the migration activation energies are the lowest for the halides followed by the A-site cations. [55][56][57][58] This results in various, and most of the time unpredictable and unforeseen, surface and bulk structures depending on the strength and polarity of the electric field.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, strong electric fields emerge at the tip/sample junction due to the mandatory voltage which must be applied to either the tip or to the sample in STM experiments. 35 These requirements pose significant challenges with respect to lead halide perovskites where the ABX 3 crystal structure (A-site: organic or inorganic cation[s], B-site: lead, C-site: halides, eg, Cl, Br, I) also mirrors the weak point in these materials: the soft, dynamic and ionic bonding character of the crystal lattice. 36,37 In this critical review, we highlight the recent progress in applying STM-based techniques to organic/inorganic and all-inorganic lead halide perovskites, both in form of single crystals and thin films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional application of CNTs is as nano-probes. Here, carbon nano-probes can be exploited as atomic force microscopy [174,175] or scanning tunnelling microscope [176,177] tips.…”
Section: Cnt-based Amperometric Transducersmentioning
confidence: 99%
“…Due to the unique electronic properties of single-walled carbon nanotubes (SWCNT) [1][2][3] , these quasi-one-dimensional materials have been widely investigated and applied in various device systems, such as field effect transistors (FET) 4 , optical switches 5 , organic photovoltaics (OPV) 6 and organic light emitting diodes (OLED) 7 . Charge dynamics at the interface between SWCNT and organic molecules/metals is of particular importance for the fundamental understanding of carbon-based electronic materials as well as for the development of new types of devices in organic electronics.…”
Section: Introductionmentioning
confidence: 99%